Perancangan Sistem Kontrol Wireless pada Mobile Robot Manipulator Berbasis Mikrokontroler ATMega8 - Zaenurrohman; Utis Sutisna (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
In this design, microcontroller ATMega8 and a wireless joystick device of the Play Station 2 are used to control a mobile robot manipulator. The wireless joystick device consists of a transmitter and receiver modules. The device is connected to the microcontroller using Serial Peripheral Interface (SPI) communication. The received data in the receiver module from the transmitter module is accessed by the microcontroller. Once received by the microcontroller, the data is used as reference in controlling various actuators in mobile robot manipulator. The results of testing, such as testing of forward and backward motion, turn right and turn left motion and the testing of manipulator motion, show that the wireless control system can control mobile robot manipulator as expected. Wireless communication between the transmitters to the receiver can be connected well at a distance of 0 to 10 meters. Meanwhile, at a distance of more than 10 meters wireless communication cannot be connected.